Investigating the impact of modernization attributes and knowledge toward sustaining Nyonya cuisines in Malacca/ Nur Nadia Maisarah Mohd Fisol and Norhidayah Abdullah - Mohd Fisol, Nur Nadia Maisarah; Abdullah, Norhidayah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study attempts to determine which of the modernization attributes effect on sustaining Nyonya cuisine in Malacca as Malaysian heritage cuisine and furthermore to identify the relationship between knowledge and sustaining Nyonya cuisine in Malacca. A self-administered survey was used to collect data from the respondents. A total of 400 questionnaires were distributed among Baba Nyonya communities in Malacca; 400 valid samples for evaluation representing a response rate of 100%. The results show that changes of production and processing method is the most affected to the sustaining Nyonya cuisine in Malacca. Since the finding shows a positive relationship between modernization attributes, knowledge and sustainability of Nyonya cuisine, Malaysia Department Heritage, Baba Nyonya Peranakan communities and individual need to emphasize these attributes to prevent the extinction of Nyonya cuisine. Hence, this study would be assisting future researchers to gain substantial insight and information in order to market and promote Nyonya cuisine in the industry as well as to sustain it.